Improving 131I Radioiodine Therapy By Hybrid Polymer-Grafted Gold Nanoparticles - Le Goas M (Dove Medical Press, 2019)
Marine Le Goas,1 Marie Paquet,2–5 Aurélie Paquirissamy,1 Julien Guglielmi,2–4 Cathy Compin,2–4 Juliette Thariat,6 Georges Vassaux,2–4 Valérie Geertsen,1 Olivier Humbert,2–5 Jean-Philippe Renault,1 Géraldine Carrot,1 Thierry Pourcher,2–4 Béatrice Cambien2–4 1NIMBE, Commissariat à l’Energie Atomique, Centre National Recherche Scientifique UMR 3685, Université Paris-Saclay, Gif-sur-Yvette, France; 2Laboratory Transporter in Imaging and Radiotherapy in Oncology (TIRO), Institut de Biosciences et Biotechnologies d’Aix-Marseille (BIAM), Commissariat à l’Energie Atomique, Nice, France; 3Laboratory Transporter in Imaging and Radiotherapy in Oncology (TIRO), University Nice Sophia Antipolis, Nice, France; 4Laboratory Transporter in Imaging and Radiotherapy in Oncology (TIRO), University Côte d’Azur, Nice, France; 5Nuclear Medicine Department, Centre Antoine Lacassagne, Nice, France; 6Department of Radiation Oncology, Centre François Baclesse, Université de Normandie, Caen, FranceCorrespondence: Béatrice CambienLaboratory Transporter in Imaging and Radiotherapy in Oncology (TIRO), University Nice Sophia Antipolis, 28 Avenue Valombrose, Nice Cedex 2 06107, FranceTel +33 493 377 715Email cambien@unice.frBackground: Human trials combining external radiotherapy (RT) and metallic nanoparticles are currently underway in cancer patients. For internal RT, in which a radioisotope such as radioiodine is systemically administered into patients, there is also a need for enhancing treatment efficacy, decreasing radiation-induced side effects and overcoming radio-resistance. However, if strategies vectorising radioiodine through nanocarriers have been documented, sensitizing the neoplasm through the use of nanotherapeutics easily translatable to the clinic in combination with the standard systemic radioiodine treatment has not been assessed yet.Method and materials: The present study explored the potential of hybrid poly(methacrylic acid)-grafted gold nanoparticles to improve the performances of systemic 131I-mediated RT on cancer cells and in tumor-bearing mice. Such nanoparticles were chosen based on their ability previously described by our group to safely withstand irradiation doses while exhibiting good biocompatibility and enhanced cellular uptake.Results: In vitro clonogenic assays performed on melanoma and colorectal cancer cells showed that poly(methacrylic acid)-grafted gold nanoparticles (PMAA-AuNPs) could efficiently lead to a marked tumor cell mortality when combined to a low activity of radioiodine, which alone appeared to be essentially ineffective on tumor cells. In vivo, tumor enrichment with PMAA-AuNPs significantly enhanced the killing potential of a systemic radioiodine treatment.Conclusion: This is the first report of a simple and reliable nanomedicine-based approach to reduce the dose of radioiodine required to reach curability. In addition, these results open up novel perspectives for using high-Z metallic NPs in additional molecular radiation therapy demonstrating heterogeneous dose distributions.Keywords: internal radioisotope therapy, radioiodine, polymer-grafted gold nanoparticles, melanoma, colorectal cancer, radio-enhancement